Effects of Policy Responses to the Spread of Covid-19 Pandemic - Briola, Helen; Briola, Konstantina (HAPSc Policy Briefs Series, 2020)
Covid-19 is a new invisible threat that has affected almost all countries of the world. In this paper we study the effects of policy responses to the spread of coronavirus pandemic. For this purpose, we utilized the dataset of Oxford Coronavirus Government Response Tracker (OxCGRT) and we examined the correlation of policies with the number of daily coronavirus cases in five countries (Greece, Italy, Spain, Sweden and United Kingdom). In order to achieve that, we calculated Kendall Correlation Coefficient and Spearman Correlation Coefficient as well as p-value for the statistical importance of our data. Our results indicate that the policies have a direct impact on the spread of Covid-19.